TECHNOLOGICAL SUPPORT OF THE DEVELOPMENT PROCESS CREATIVE THINKING OF A FUTURE TEACHER - Akimova, O.V. (Pedagogy of Higher and Secondary Education, 2007)
This article deals with modern pedagogical technologies and the author’s approach to the development of the future teacher’s creative personality on the basis of development of creative pedagogical thinking are suggested.